Analysis of Small Nuclear RNAs in a Precatalytic Spliceosome - Yean, Shyue-Lee (Gene Expr, 2018)
U1 small nuclear RNA plays an important role in early stages of intron recognition and spliceosome assembly. The 5′ splice site of the premessenger RNA base-pairs with the 5′ end of Ul; however, that interaction appears to be replaced by U5 and U6 at later stages of the splicing process. It has not been established when this transition occurs nor what factors are required for the transition. The PRP2 gene of Saccharomyces cerevisiae encodes an RNA-dependent ATPase that belongs to the DEAH putative RNA helicase family. A spliceosome can be assembled in the absence of PRP2 but the ATPase activity of PRP2 is required for the onset of the catalytic reactions in the spliceosome. By probing the precatalytic spliceosome formed in temperature-sensitive prp2 mutant extracts with oligonucleotides complementary to snRNAs, we found that the 5′ end of Ul was sensitive to RNase H digestion whereas the 5′ splice site-interacting region of U6 became resistant. Furthermore, by treating with heparin, a spliceosome depleted of Ul snRNA was isolated that subsequently underwent splicing with additional protein factors and ATP. Thus, these results indicate that PRP2 is not responsible for the transition from Ul to U6 in the spliceosome and that the entire Ul snRNA is not involved in the catalytic phase of pre-mRNA splicing.